2013
DOI: 10.1179/1743132813y.0000000275
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin associated intracerebral hemorrhage in Hong Kong Chinese

Abstract: Warfarin-associated intracerebral hemorrhage is a very serious complication of warfarin therapy with high mortality and morbidity. Initial ICH volume, presence of intraventricular hemorrhage, and ND are independent predictors of clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Proportionally the ratio between ischaemic stroke to haemorrhagic stroke is lower in Asians compared to nonAsians [21]. Also, Asian patients have a higher mortality due to warfarin-induced intra-cranial haemorrhage (ICH) (62%) compared to Caucasians [22]. Nonetheless, the higher risks associated with Asians may not be a problem solely with warfarin.…”
Section: Epidemiology -A Brief Overviewmentioning
confidence: 97%
“…Proportionally the ratio between ischaemic stroke to haemorrhagic stroke is lower in Asians compared to nonAsians [21]. Also, Asian patients have a higher mortality due to warfarin-induced intra-cranial haemorrhage (ICH) (62%) compared to Caucasians [22]. Nonetheless, the higher risks associated with Asians may not be a problem solely with warfarin.…”
Section: Epidemiology -A Brief Overviewmentioning
confidence: 97%
“…Of the remaining 17 articles, 9 were excluded because they were only about anticoagulants [24][25][26][27][28][29][30][31][32], one was excluded because the majority of participants who had resumed antithrombotic agents had their medicine terminated or changed during the follow-up [33], and one was excluded because there was no clear record of which kind of antithrombotic agents, oral anticoagulant, or AP therapy was resumed [34]. Finally, only 6 articles met the inclusion criteria [35][36][37][38][39][40]. The study selection is presented in flow chart form in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The 6 studies offered data containing 1916 patients (825 in AP resumption group, 1091 in non-AP resumption group) [35][36][37][38][39][40]. Pooled result using the random-effects model showed that there was no significant difference between AP resumption group and non-AP resumption group for ICH recurrence or hematoma expansion (RR, 0.84; 95% CI, 0.47-1.51; P = 0.56) (Fig.…”
Section: Ap Resumption Did Not Significantly Increase Ich Recurrence mentioning
confidence: 99%
“…Included studies were published from 2005 to 2016, and sample sizes ranged from 20 23 to 1752 participants, 25 with the length of follow-up ranging from 12 17 20 24–27 to 55 months 21 ( table 1 , online supplementary table S2 ). The type of oral anticoagulants received at the time of ICH occurrence was VKA in all studies, with the exception of De Vleeschouwer et al 17 (the type of anticoagulation was not reported) and Nielsen et al 25 (some participants received NOAC).…”
Section: Resultsmentioning
confidence: 99%